Pleiotropic effect of the TPH A779C polymorphism on nicotine dependence and personality - Reuter, M.; Hennig, J. (American journal of medical genetics. Part B, Neuropsychiatric genetics, 2005)
Recent studies from molecular genetics have suggested an association between the tryptophan hydroxylase 1 (TPH1) gene and nicotine addiction indicating a dysfunction of the serotonergic (5‐HT) system in smoking behavior. In a sample of 252 healthy subjects, a significant association between variations observed in nicotine dependence and the heterozygous AC‐genotype of the TPH A779C polymorphism could be demonstrated. Moreover, the heterozygous genotype was significantly associated with a personality trait of neurotic aggression (indirect hostility, negativism), as measured by the Buss–Durkee‐Hostility‐Inventory (BDHI). The positive heterosis effects with respect to nicotine addiction and personality support the idea that the TPH1 gene exerts pleiotropic effects. © 2004 Wiley‐Liss, Inc.